2022
DOI: 10.1111/bjd.21710
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with central centrifugal cicatricial alopecia: a preliminary study

Abstract: Central centrifugal cicatricial alopecia (CCCA) is a common cause of hair loss among patients of African and/or Caribbean descent, and there is little data exploring the quality of life of patients with this condition. This pilot demonstrates that CCCA has a significant impact on overall quality of life, and patients may benefit from resources to address psychosocial aspects of this diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 6 publications
(5 reference statements)
0
10
0
Order By: Relevance
“…A disease‐specific tool CCCA‐QLI, employed by Maranga et al, 20 in 56 patients with CCCA, showed an impaired life quality with a mean QoL of 53.31 on a scale of 0 (best) to 100 (worst), where a score > 50 indicates a significant impairment of quality of life. Scores in subjective symptoms and objective signs, two of the three sections of the CCCA‐QLI, suggest considerably reduced quality of life (77.0 and 60.7, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A disease‐specific tool CCCA‐QLI, employed by Maranga et al, 20 in 56 patients with CCCA, showed an impaired life quality with a mean QoL of 53.31 on a scale of 0 (best) to 100 (worst), where a score > 50 indicates a significant impairment of quality of life. Scores in subjective symptoms and objective signs, two of the three sections of the CCCA‐QLI, suggest considerably reduced quality of life (77.0 and 60.7, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…The studies investigated QoL in the following conditions: cicatricial alopecia ( n = 4), 15,24,29,30 LPP ( n = 2), 26,27 LPP and FFA ( n = 2), 17,25 FFA ( n = 3), 21,23,28 FD ( n = 1), 22 and CCCA ( n = 2) 19,20 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations